Amino acids and BCAA composition of Mungbean (Vigna radiata L.) seeds and sprouts for plant-based protein applications - Chanwook Kim; Seyoung Jeon; Yeon-Ji Jo; Jungmin Ha (Scientific Reports)
Abstract Plant-based proteins from legume crops are emerging as sustainable alternatives to animal proteins and as nutritional ingredients in various food products. Mungbeans (Vigna radiata L.) are rich in essential amino acids and have a high protein content. This study investigated changes in total amino acids, branched-chain amino acids (BCAA), vitamins, and antioxidants for five days after germination. The amino acid and BCAA content of mungbeans varied depending on the genotype, and the amino acid composition changed during cultivation. Mungbeans in the early stages of germination had significantly higher total amino acid and BCAA contents than seeds. The antioxidant capacity and content of vitamin B-complex and vitamin C, but not thiamine, also increased significantly after germination. Among the 18 genotypes, Bohabe Yellow Mongo had the highest amino acid and BCAA contents in the early stages of germination, while Dahyeon showed high amino acid and BCAA contents in the seed state and high vitamin C content after germination. The seeds of 742, a wild genotype, showed high antioxidant capacity, especially high thiamine content. These findings indicated the importance of selecting appropriate varieties and cultivation times when cultivating mungbean as a source of plant-based proteins.